2014
DOI: 10.1002/app.40743
|View full text |Cite
|
Sign up to set email alerts
|

MgCl2‐supported Ziegler–Natta catalyst containing dibenzoyl sulfide donor for propylene polymerization

Abstract: Polypropylene (PP) was synthesized in the presence of Ziegler-Natta catalysts composed of MgCl 2 -TiCl 4 -internal donor/ AlR 3 -external donor. Diisobutyl phthalate is a well-known internal donor in current PP production. Nevertheless, phthalates are often blamed as endocrine disruptors. The objective is to find an ecofriendly internal donor producing PP with maintaining its physical properties. When using dibenzoyl sulfide, synthesized PP shows the superiority to diisobutyl phthalate in the activity of catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The two surfaces differ in coordination of the surface magnesium atoms; the (104) surface features five-coordinate magnesium atoms, whereas the (110) surface features four-coordinate magnesium atoms (Figure ). , The unsaturated magnesium atoms generate adsorption sites for titanium tetrachloride and electron donors . Adsorbed titanium tetrachloride transforms into polymerization active sites through activation by the cocatalyst. Electron donors, which are added during the catalyst preparation, have an influence on the morphology of the catalyst support as well as on the distribution and stereoselectivity of the active sites. …”
Section: Introductionmentioning
confidence: 99%
“…The two surfaces differ in coordination of the surface magnesium atoms; the (104) surface features five-coordinate magnesium atoms, whereas the (110) surface features four-coordinate magnesium atoms (Figure ). , The unsaturated magnesium atoms generate adsorption sites for titanium tetrachloride and electron donors . Adsorbed titanium tetrachloride transforms into polymerization active sites through activation by the cocatalyst. Electron donors, which are added during the catalyst preparation, have an influence on the morphology of the catalyst support as well as on the distribution and stereoselectivity of the active sites. …”
Section: Introductionmentioning
confidence: 99%
“…9–11 Cooperation between internal and external donors contributes to the catalyst's activity and the isotacticity of polypropylene. 12–14…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the fourth-generation catalyst containing diisobutyl phthalate (D i BP, the commercial internal donor), the bioderived diesters have reasonable activity and stereospecificity in propylene polymerization . The dibenzoyl sulfide donor and the eco-friendly salicylate donor were reported to show superiority to D i BP in terms of catalytic activity and isotacticity of polypropylene. , Nissinen et al first reported the multidentate donor polyethylenimine, an amino-functional polymer, was used as an internal donor in the copolymerization of ethylene/1-butene and showed high catalytic activity. DFT results showed that branched polyethylenimines could stabilize the MgCl 2 (104) surface through primary amino groups .…”
Section: Introductionmentioning
confidence: 99%